Exploring the Application of Artificial Intelligence (AI) Tools in the Operations of Hotels in the Jos Tourism Sector in the Post-COVID-19 Period - Majebi, Enesi Chukwuemeka (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
Artificial Intelligence (AI) tools have improved the operations of multiple tourism sectors, including hotel accommodation, attractions, transportation, travel agencies, and food and beverages in the post-COVID-19 period. Nonetheless, it does not seem that there is evidence of any study investigating the application of AI in the hotel sector of a developing destination’s tourism industry, like Jos, Plateau State, Nigeria, in the post-COVID-19 period. This article employs a semi-structured/In-depth interview technique to explore the perspectives of hotel accommodation stakeholders, including 7 hotel managers, 3 tourism industry sector consultants, and 2 academics in the Jos Metropolitan area of Plateau State, Nigeria, on the use of AI to improve their operations in the post-COVID-19 period. Data derived were descriptively analyzed based on themes on the uses of AI to enhance hotel business efficiency. The research revealed the efficiency of AI tools in the selected Jos hotels and the hindrances to their use, including customers’ personal privacy concerns, and poor patronage due to the current economic and security crisis. The article has implications for suggesting efficient measures for adopting AI technologies, including facial recognition, and mobile app/card entry for revenue generation, improving security and customer services in similar and other sectors of Nigeria’s tourism industry